1983
DOI: 10.1016/0370-2693(83)90821-3
|View full text |Cite
|
Sign up to set email alerts
|

Deconfinement and virtual quark loops

Abstract: We calculate per Monte Carlo evaluation on an 83 × 3 lattice the energy density e G of the gluon sector of QCD, including virtual quark loops up to the fourth power in the hopping parameter expansion. For light quarks of one flavour, we observe at T/A L ~ 95 -+ 10 a rapid variation of e G in T, accompanied by strong fluctuations from iteration to iteration, as clear signal of the deconfinement transition.The deconfinement transition, at which strongly interacting matter becomes a colour-conducting plasma, has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…As in QCD with fermions [12][13][14] at finite temperature and low K we find persistence of the first-order deconfinement transition of the pure SU(3) gauge model. But we also find first-order transitions by varying K at fixed/3, corresponding to a transition between "broken" and "unbroken" phases.…”
Section: Resultssupporting
confidence: 53%
“…As in QCD with fermions [12][13][14] at finite temperature and low K we find persistence of the first-order deconfinement transition of the pure SU(3) gauge model. But we also find first-order transitions by varying K at fixed/3, corresponding to a transition between "broken" and "unbroken" phases.…”
Section: Resultssupporting
confidence: 53%
“…As pointed out earlier, the implications of these results for SU (2) and SU(3) are quite interesting and it would thus be nice to see whether such coexistence of phases can also be found for the SU(3) theory which is also predicted to have a first order transition on the basis of exactly the same arguments which predict the Z(3) transition to be of first order [4]. Though so far no evidence has been presented in the literature for coexisting phases in the case of SU(3) to support the claim that its transition is of first order, we understand that work is in progress and will be reported soon [5,13].…”
Section: Rnu Nusupporting
confidence: 67%
“…The discontinuity in /S decreases with decreasing quark mass (increasing external field), and based on strong coupling arguments it has been suggested that the deconfinement transition may be completely washed out in the light-quark limit [6][7][8][9]. However, all quantitative studies performed so far [10][11][12][13] continue to show a very abrupt deconfinement transition even for the lightest quark masses considered.…”
Section: Introductionmentioning
confidence: 98%